2017
DOI: 10.3389/fcvm.2017.00015
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Investigations for the Diagnosis of Fontan-Associated Liver Disease in Pediatric and Adult Fontan Patients

Abstract: Fontan-associated liver disease (FALD) is a serious complication related to the chronically elevated venous pressure and low cardiac output of this abnormal circulation. However, diagnostic markers for this condition are limited. We hypothesized that specific tests for fibrosis developed for other chronic liver diseases would identify a higher prevalence of FALD than ultrasound and standard laboratory tests and that identified abnormalities would correlate with time post-Fontan. In this cross-sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Recently, Friedrich‐Rust et al demonstrated that the peripheral biomarkers Fibrotest/Fibrosure and Actitest (Biopredictive, Paris, France) successfully detected the presence of liver fibrosis and correlated with disease progression in Fontan patients. Fidai et al reported similar results in a study that included pediatric and adult Fontan patients. However, a recent report by Wu et al showed that Fibrosure (LabCorp, Burlington, NC, USA) and hyaluronic acid did not correlate with the degree of hepatic fibrosis and did not predict cirrhosis in a population of adult Fontan patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recently, Friedrich‐Rust et al demonstrated that the peripheral biomarkers Fibrotest/Fibrosure and Actitest (Biopredictive, Paris, France) successfully detected the presence of liver fibrosis and correlated with disease progression in Fontan patients. Fidai et al reported similar results in a study that included pediatric and adult Fontan patients. However, a recent report by Wu et al showed that Fibrosure (LabCorp, Burlington, NC, USA) and hyaluronic acid did not correlate with the degree of hepatic fibrosis and did not predict cirrhosis in a population of adult Fontan patients.…”
Section: Discussionsupporting
confidence: 53%
“…Along with ultrasound, computed tomography and magnetic resonance imaging have been evaluated. More recently, measures of liver stiffness have been utilized to identify liver fibrosis in Fontan patients, including transient elastography, ARFI, and SWE . Although liver imaging and measures of liver stiffness have been shown to accurately identify abnormal liver architecture, these findings often do not correlate with clinical features and synthetic liver function in Fontan patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we previously reported a significant correlation in Fontan patients between TFS and MELD‐XI scores . Additionally, past reports, by others and by us, had noted increasing fibrosis scores with time post‐Fontan . Nevertheless, time data had significant variability.…”
Section: Discussionmentioning
confidence: 61%
“…Fidai et al used both TE with FibroSURE to assess for signs of FALD in a group of children and adults. They noted a significant correlation between the degree of liver stiffness and time post‐Fontan.…”
Section: Discussionmentioning
confidence: 99%